The Potential of Electrical Stimulation and Smart Textiles for Patients with Diabetes Mellitus - Engler, Babette; Tselmin, Sergey; Ziehl, Doreen; Weigmann, Ingo; Birkenfeld, Andreas; Bornstein, Stefan R.; Barthel, Andreas; Drechsel, Tina; Zippenfennig, Claudio; Milani, Thomas; Perakakis, Nikolaos (Hormone and Metabolic Research, 2022)
Diabetes mellitus is one of the most frequent diseases in the general population. Electrical stimulation is a treatment modality based on the transmission of electrical pulses into the body that has been widely used for improving wound healing and for managing acute and chronic pain. Here, we discuss recent advancements in electroceuticals and haptic/smart devices for quality of life and present in which patients and how electrical stimulation may prove to be useful for the treatment of diabetes-related complications.
Keywords: diabetes; neuropathy; electroceuticals